The impact of hemovigilance studies on transfusion practices: Single centre experience - Samet Yaman; Gökhan Evren; Bilge Zihar; Emine Beköz; Yurdagül Kökcü; Abdulkerim Yıldız (Hitit Medical Journal)

(untitled)
Objective: Blood product transfusion is one of the most commonly used medical interventions worldwide. However, transfusion-related adverse events (TRAEs) can cause morbidity and rarely even mortality. For this reason, hemovigilance studies have recently gained importance in terms of safe and effective implementation of transfusion.Material and Method: Transfusion practices issued in the period of 2016-2023 were analyzed retrospectively. All TRAE including adverse reactions (AR) and adverse events (AE) were recorded. The impact of hemovigilance practices on the incidence of TRAE was analyzed by comparing the numbers and types of events between years.Results: In the 8-year period between 2016 and 2023, a total of 135,506 blood products belonging to 45,571 patients were used. 172 adverse reactions (AR) were reported in 170 patients. The overall AR incidence was found to be 126.8 (/100000). The highest yearly AR rate was reported in 2018 with 168.04 (/100000). Since hemovigilance measures were tightened, a statistically significant decrease was recorded in ARs from the beginning of 2020 to date (p